Moral Values in The Little Prince as Character Education in Vocational High School - Pradikta, Rahma Dian; Yudi Cahyono, Bambang (International Journal of Language Teaching and Education, 2026)
This study explores the moral values in Little Prince by Antoine de Saint-Exupery in correlation to character education in Vocational High School. It is connecting with the learning outcomes of Indonesian subjects in Phase E of the Independent Curriculum (Kurikulum Merdeka). This research is a descriptive qualitative study, with data collection using documentation techniques. The data was in from the story quotes that show the moral values, taken from the data source: the novella. Data analysis using an interactive approach. The results of the study are: (1) the positive moral value, and (2) the moral values can be utilized in character education and are in line with the achievements of Indonesian language learning in Phase E of the Curriculum